Exploratory Acoustic Investigation of Customizable 3D-Printed Hybrid Acoustic Materials (HAMs) through Interlaboratory Impedance Tube Measurements - Vaia Tsiokou; Louena Shtrepi; Elena Badino; Arianna Astolfi; Anna Karatza (Acoustics, 2023)
Acoustic materials are widely used for improving interior acoustics based on their sound absorptive or sound diffusive properties. However, common acoustic materials only offer limited options for customizable geometrical features, performance, and aesthetics. This paper focuses on the sound absorption performance of highly customizable 3D-printed Hybrid Acoustic Materials (HAMs) by means of parametric stepped thickness, which is used for sound absorption and diffusion. HAMs were parametrically designed and produced using computational design, 3D-printing technology, and feedstock material with adjustable porosity, allowing for the advanced control of acoustic performance through geometry-related sound absorbing/diffusing strategies. The proposed design methodology paves the way to a customizable large-scale cumulative acoustic performance by varying the parametric stepped thickness. The present study explores the challenges posed by the testing of the sound absorption performance of HAMs in an impedance tube. The representativeness of the test samples (i.e., cylindrical sections) with respect to the original (i.e., rectangular) panel samples is contextually limited by the respective impedance tube’s geometrical features (i.e., cylindrical cross-section) and dimensional requirements (i.e., diameter size). To this aim, an interlaboratory comparison was carried out by testing the normal incidence sound absorption of ten samples in two independent laboratories with two different impedance tubes. The results obtained demonstrate a good level of agreement, with HAMs performing better at lower frequencies than expected and behaving like Helmholtz absorbers, as well as demonstrating a frequency shift pattern related to superficial geometric features.